1989
DOI: 10.2166/wqrj.1989.006
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of Trace Metals in Three Species of Fish from Lakes in New Brunswick and Nova Scotia (Canada): Influence of pH and Other Chemical Parameters

Abstract: Brook trout (Salvelinus fontinalis), white sucker (Catostomus commersonii) and yellow perch (Perca flavescens) from headwater lakes in New Brunswick and Nova Scotia (Canada) were analyzed for whole body concentrations of Pb, Cd, Hg, Cu and Zn. Fish from western New Brunswick generally had lowest concentrations of metals. Mercury concentrations were highest in fish from lakes close to urban centers on the leeward side. Only trout were collected from lakes in Cape Breton Island, and these were characterized by h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Mercury levels in freshwater fish in Atlantic Canada are correlated with lake acidity and dissolved organic carbon concentrations (Peterson et al, 1990;Carter et al, 2001;Rencz et al, 2003;Drysdale et al, in press). Loons in Atlantic Canada frequently nest on low-pH, lowalkalinity, oligotrophic lakes (Kerekes, 1990;Burgess et al, 1998a;Hope, this volume); such lakes tend to have elevated fish Hg levels (Wiener et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Mercury levels in freshwater fish in Atlantic Canada are correlated with lake acidity and dissolved organic carbon concentrations (Peterson et al, 1990;Carter et al, 2001;Rencz et al, 2003;Drysdale et al, in press). Loons in Atlantic Canada frequently nest on low-pH, lowalkalinity, oligotrophic lakes (Kerekes, 1990;Burgess et al, 1998a;Hope, this volume); such lakes tend to have elevated fish Hg levels (Wiener et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…This is confirmed by elevated Hg concentrations found in common loon eggs (Scheuhammer et al, 2001) and in organ tissues of dead loons (Daoust et al, 1998) recovered in Atlantic Canada. Several studies have found elevated Hg levels in freshwater fish in Atlantic Canada, especially in lakes with low pH and high dissolved organic carbon concentrations (Peterson et al, 1990;Carter et al, 2001;Rencz et al, 2003;Drysdale et al, 2005;Kamman et al, 2005), which are common in the region. All of these fish-Hg studies included yellow perch (Perca flavescens), which is the preferred prey of common loons (Barr, 1996).…”
Section: Introductionmentioning
confidence: 99%